(untitled) (Journal of the College of Basic Education, 2026)
This research aims to identify the effect of the Gerlack and Ely model on developing visual intelligence and skill performance among students at the Institute of Fine Arts in the subject of Design Techniques. The experimental design, a quasi-experimental design with two independent and equivalent groups, was used. The research sample consisted of (40) students randomly selected from the study population, divided into two groups: (20) students in the experimental group and (20) students in the control group. The researcher prepared a visual intelligence scale consisting of (10) items, a cognitive achievement test consisting of (20) items, and a skills test. To evaluate student performance, a skills performance evaluation form consisting of (10) items was developed and its validity and reliability were verified. Appropriate statistical methods were used, including the t-test and Kuder-Richardson’s coefficient of 20. After administering the instrument to the research sample and statistically analyzing the results, the findings revealed statistically significant differences at the (0.05) level between the mean scores of the experimental group students, who studied according to the Gerlach-Ely model, and the mean scores of the control group students, who studied according to the traditional method, on the visual intelligence scale, the cognitive achievement test, and the skills performance test. After the Design Techniques course and for the benefit of the experimental group.